VIRTUAL HOTEL OPERATOR; IS IT DISRUPTION FOR HOTEL INDUSTRY? - Rachel Dyah Wiastuti; Erna Mariana Susilowardhani (Jurnal Hospitality dan Pariwisata, 2017)
Virtual Hotel Operator (VHO) concept in Indonesia has been rising in 2015. The first VirtualHotel Operator in Indonesia is Nida Rooms, and more are coming in numbers such as AiryRooms, RedDoorz, Zen Rooms and Tinggal. Economic to mid accommodation and lodgingbecome the main target partner for Virtual Hotel Operator, either in strategic or remotecities in Indonesia. Less research provide data either VHO concept arises as disruption ornot. The purpose of this paper is to examine Virtual Hotel Operator concept towardsdisruption in hotel industry. This is qualitative exploratory research. Literature study anddocumentation are applied as primary data sources. Lack of journal related to Virtual HotelOperator concept acquired data obtained from news and articles. As the results, detaildescriptions about Virtual Hotel Operator are elaborate; definition, concept, characteristic,advantages and disadvantages, target partner, target customer, the way it works, as well asthe analysis either Virtual Hotel Operator comply as disruption in hotel industry or not. Thispaper contributes to broaden Virtual Hotel Operator concept in the new era of hotel industry.Further study should be conducted by involving Virtual Hotel Operator managementrepresentative and people who are Virtual Hotel Operator‟s userKeywords: Virtual Hotel Operator, VHO, budget hotel, hotel operator